Effect of Sertraline on biomarker alterations in patients of multidrug resistant tuberculosis with depression: a prospective clinical trial - Singh, Vijay Kumar; Kushwaha, Virendra; Agrawal, Pooja; Gupta, Ambrish; Kumar, Amit; Chaudhari, Dhananjay; Kumar, Anand; Bindal, Mahesh Chandra (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Lipid profile parameters may be used as biomarker for depression. Sertraline belongs to selective serotonin reuptake inhibitors (SSRIs), the most commonly used group to treat the depression in multidrug resistant tuberculosis patients. Methods: A prospective clinical trial was carried out in department of Psychiatry and department of Tuberculosis and Respiratory disease G.S.V.M. Medical College, Kanpur. Diagnosed MDR TB patients were screened for depression applying Hamilton Depression Rating Scale (HDRS) and these patients were referred to Psychiatrist for diagnosis of depression. Total 25 diagnosed patients of MDR TB with mild to moderate depression were selected. HDRS Score and morning blood sample of 5ml were collected to analyze biomarker for depression before intervention. Same test was repeated in 18 patients who completed the study at day 30 and 120 after administering Sertraline (50mg). Data were compiled and analyzed using SPSS 20.0 and paired t - test. Results: The mean decrease in HDRS score from base line at day 30 and 120 of administering Sertraline were 6.22 (±1.26) and 2.72 (±0.67) which were significant (p˂0.001). The mean increase in serum cholesterol at day 30 was 153.94 (±19.31) and at day 120 was 157.83 (±19.36) which were significant (p˂0.001). Rest of Tg, HDLc, LDLc and VLDL cholesterole levels were not increased significantly. Conclusions: As the depression symptoms improved by sertraline. The biomarkers of depression were also increased (within the normal range) from baseline but significant increase was observed in serum cholesterol only.